Iman dan Kesehatan Psikis Perspektif Said Nursi (Kajian Psikoterapi dalam Risale-i Nur) - Hamid Fahmy Zarkasyi; Jarman Arroisi; Amal Hizbullah; Dahniar Maharani (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2020)
This paper try to reveal the approach used by Badi’uzzaman Said Nursi in Islamic Psychotherpy discourse, and try to undestand his method in mantaining morals and spirituals value and bettering it.  Also this paper is aimed to focus on Nursi’s approach and method that differentiate him from other Muslim schoolar and psychologist. The approach bacground will be disscused here as well as it reason and aim of Nursi’s approach toward this issue. Nursi’s works is not merely an intelectual contemplation but as a direct respons to various problems he faced and is faced by Turkish society at that time. This paper use qualitative methode (library research) which focused to respon the main problem. Therefore, it is critical to put his works into context of faith which is the guidence of live. With his works, Risale-i Nur, Said Nursi introduce Metode Imani answering and giving solutions to moral degradation that spread all over the world. His approach in psychotherapy develop  a deep understanding about the concept of faith and its impact upon the live.